2011
DOI: 10.1159/000327017
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Prenatal Psychobiological Stress Exerts Programming Influences on the Mother and Her Fetus

Abstract: Background/Aims: Accumulating evidence from a relatively small number of prospective studies indicates that exposure to prenatal stress profoundly influences the developing human fetus with consequences that persist into childhood and very likely forever. Methods: Maternal/fetal dyads are assessed at ∼20, ∼25, ∼31 and ∼36 weeks of gestation. Infant assessments begin 24 h after delivery with the collection of cortisol and behavioral responses to the painful stress of the heel-stick procedure and measures of neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
199
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(217 citation statements)
references
References 288 publications
13
199
0
2
Order By: Relevance
“…Furthermore, studies indicate that some women are particularly sensitive to hormonal fluctuations, thus increasing their susceptibility to psychological stressing agents that are triggered by environmental and physiological factors [55] . Preterm birth has been identified as one potential outcome of fetal exposure to stress during pregnancy, and is further associated with a host of negative consequences for the fetus and subsequent development [56] . Complementary therapeutic interventions (e.g.…”
Section: Biological Factors Associated With Perinatal Healthmentioning
confidence: 99%
“…Furthermore, studies indicate that some women are particularly sensitive to hormonal fluctuations, thus increasing their susceptibility to psychological stressing agents that are triggered by environmental and physiological factors [55] . Preterm birth has been identified as one potential outcome of fetal exposure to stress during pregnancy, and is further associated with a host of negative consequences for the fetus and subsequent development [56] . Complementary therapeutic interventions (e.g.…”
Section: Biological Factors Associated With Perinatal Healthmentioning
confidence: 99%
“…Intrauterine conditions that affect these structures and also are associated with increased risk for neuropsychiatric disorders include infection (9), maternal undernutrition (10,11), unhealthy maternal behaviors such as smoking or alcohol or drug use (12)(13)(14), and excessive maternal stress exposure (15). We and others have suggested that glucocorticoids (cortisol in humans) may play a salient role in this process (16)(17)(18). First, cortisol, the end-product of the hypothalamic-pituitary-adrenal (HPA) axis, is known to exert a wide array of metabolic, endocrine, and immune effects on most if not all cells (19,20), and is known to play a key role in events underlying the development of the brain and other organ systems (16).…”
mentioning
confidence: 99%
“…Maternal forecasting by induction of a specific developmental trajectory is thought by many researchers to be important in human biology (for example, Bateson, 2001;Gluckman and Hanson, 2004;Sandman et al, 2012). The individual benefits, it is argued, by adjusting the trajectory of his or her development so that the developed phenotype is most likely to match the anticipated environment.…”
Section: Conditional Plasticitymentioning
confidence: 99%